Republic of Tajikistan : 2006 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV Consultation on the Republic of Tajikistan explains political and economic developments. Although Tajikistan's external debt profile has improved significantly, total public and publicly guaranteed debt is projected to increase significantly, mainly because of large project-related disbursements from China. Any financial resources directed to the private sector, particularly if subsidized, should be channeled through the budget in a transparent manner. Executive Directors welcomed the authorities' intention to put in place a debt management strategy that will prevent public debt from exceeding 60 percent of GDP.